Monoclonal Antibodies and Their Functional Fragments in Research, Diagnosis and Therapy (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book is a compendium of scientific articles submitted to a Special Issue of International Journal of Molecular Sciences, fostered by MDPI and curated by Dr. Annamaria Sandomenico and Dr. Menotti Ruvo from the Institute of Biostructure and Bioimaging of the National Research Council. All articles underwent a rigorous peer review and were selected to highlight the properties that make monoclonal antibodies and their functional fragments some of the most useful and versatile assets in therapy and diagnosis.